O sistema de informação nas instituições públicas de ensino superior: o caso da Pró-Reitoria de Ensino e Graduação da Universidade do Amazonas - Cerquinho, Kleomara Gomes (2001)
The aims of this thesis was to investigate if the information resources of the ProRectory of Graduation at the University of Amazonas - PROEG - are properly being used, to examine the doubts to make use of, to reduce deficiencies, and to suggest changes. For this purpose bibliographies in information systems management and the existent documents were analyzed and a field research was undertaken. The last two subjects will be the main guidelines for perfecting the service since just by means of them it will actually make known how occurs the information processo A distinct utilization or changes to information systems of PROEG hypotheses should provide viable suggestions for improving the duty, in order that this research is validated.